5+2m=7m+5

Simple and best practice solution for 5+2m=7m+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5+2m=7m+5 equation:


Simplifying
5 + 2m = 7m + 5

Reorder the terms:
5 + 2m = 5 + 7m

Add '-5' to each side of the equation.
5 + -5 + 2m = 5 + -5 + 7m

Combine like terms: 5 + -5 = 0
0 + 2m = 5 + -5 + 7m
2m = 5 + -5 + 7m

Combine like terms: 5 + -5 = 0
2m = 0 + 7m
2m = 7m

Solving
2m = 7m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-7m' to each side of the equation.
2m + -7m = 7m + -7m

Combine like terms: 2m + -7m = -5m
-5m = 7m + -7m

Combine like terms: 7m + -7m = 0
-5m = 0

Divide each side by '-5'.
m = 0

Simplifying
m = 0

See similar equations:

| 0.25(2x+6)=7x | | 3(x-6)=6.9 | | 4x+2y=6 | | 9(a+3)=41.4 | | 1=3c-8 | | 119-4x=5x+20 | | 6x+7=55 | | 8y-3=4y+(11-3y) | | -25-4x=11-8x | | 4e-3=-1.4 | | -7+6x=11 | | -119-10x=10x+21 | | 73-3x=7x+23 | | -x+21=15 | | -9x+28=-6x+49 | | 4(4x+3)=2(7x+6) | | 6x+12=-116-10x | | -12=2(x-1) | | 2+3(3n-1)=26 | | 8(4x-7)=16x | | 7x-4=x-28 | | 6x+15=x+30 | | 3(3+5x)-3=51 | | 106-4x=32+18 | | 6x-2=13x-23 | | -14-4x=10-8x | | 3x+6=4x+3 | | 6-8x=201-43x | | -x+15=21 | | y=nx+a | | 14+2x=x-9 | | 3x+1-4x=4-(x+3) |

Equations solver categories